Analysis of the Risks Experienced by Islamic Financial Institutions: A VOSviewer Bibliometric Approach - Suminto, Ahmad; Uddin, Mohammad Syifa; Sujianto, Agus Eko; Aswad, Muhammad; Asiyah, Binti Nur; Muhammad, Atha Mahdi (MALIA: Journal of Islamic Banking and Finance, 2025)
This study aims to analyse and map the development of literature on risk analysis in Islamic financial institutions. The data used in this study is secondary data obtained from scientific journal articles. The data source for this study is the academic database Google Scholar. The Publish or Perish (PoP) software was used to collect data, and the data analysis tools employed in this study included Microsoft Excel, Mendeley Desktop, and VOSviewer. Data collection from the PoP application from 2016 to 2025 yielded 997 articles from both international and national journals, totalling 17,030 citations, with an average of 1,892 citations per year and 17 citations per article. The results of the network visualisation map obtained 287 keywords divided into 18 clusters, 3,110 links, and a total link strength of 6,596, arranged in a collection of grouped and interconnected colored circles. In this study, network visualisation analysis of research themes and trends reveals the evolution of thinking from theoretical aspects to practical applications. In contrast, citation analysis highlights the topics most widely considered in the literature. The analysis in this study includes article publication citation analysis, bibliometric network visualisation analysis based on keywords, bibliometric overlay visualisation analysis, keyword classification analysis, and link strength analysis in the type of co-occurrence analysis, as well as bibliometric analysis on research flows (gap research). From these stages of analysis, three recommendations for further research are mapped.